The Effect of Hope on The Psychological Well-Being of Police Officers in Perak - Adibah Abdul Kadir; Eta Wahab; Fadillah Ismail; Istimaroh; Fatimatuzzahro Amin (Journal of Social Transformation and Regional Development, 2025)
The psychological well-being of police officers is a critical area of research, particularly given the unique challenges and stressors associated with law enforcement work. Police officers are prone to witnessing shocking incidence and exposure to traumatic events which can therefore put them at risk of stress disorders; such include PTSD and other psychological conditions. This will impact police officers individually as well as the organization in its unit interactions with the community. In this regard, it is important to understand the mechanisms through which hope promotes psychological wellbeing. Research shows that encouraging hope can benefit police officers' resilience, mental health, and job satisfaction—all of which are critical for preserving their efficacy and wellbeing in high-stress situations. This study intends to investigate the effect of hope on psychological well-being. 137 police officers from Perak participated in this study. The approach used is quantitative by using online survey questionnaire by utilizing random sampling technique. Statistical Package for the Social Science (SPSS) software was used to analyze the collected data. The findings show that police officer in Perak has high level of psychological wellbeing. Hope showed significant relationship with psychological well-being. Future studies should investigate how police forces may optimize hope for varying demographic groups in order to improve psychological well-being in general.